Laboratory Identification of Pseudohypercalcemia Induced by Hyperglobulinemia in Multiple Myeloma: A Case Report - Anjiang Zhao; Fan Zhong; Yankui Liu; Guixing Li (Journal of Clinical Laboratory Analysis, 2026)
ABSTRACT Background Pseudohypercalcemia is easily misdiagnosed in clinical practice, potentially leading to unnecessary interventions. Multiple myeloma (MM) presenting with concurrent hypergammaglobulinemia represents a rare etiology of pseudohypercalcemia, and there are few reports of systematic laboratory validation of this pathological entity. Methods We report a patient with MM who presented with markedly elevated serum total calcium on routine biochemical testing. The hypercalcemia persisted despite 1 month of calcitonin therapy administered at an external hospital. After admission, the clinical laboratory team performed a panel of confirmatory assays, including direct ionized calcium measurement, post‐dilution linearity evaluation, inductively coupled plasma mass spectrometry (ICP‐MS) verification, and polyethylene glycol (PEG) precipitation testing. Results and Conclusions The results confirmed that the elevation in serum total calcium was attributed to enhanced calcium binding to circulating globulins, secondary to hypergammaglobulinemia, rather than analytical interference in the detection system. During clinical follow‐up, serum total calcium levels normalized progressively in parallel with the decline in globulin levels following targeted anti‐myeloma therapy. This case demonstrates that clinicians and laboratory professionals should maintain a high index of suspicion for pseudohypercalcemia when encountering patients with marked paraproteinemia or abnormal circulating macromolecules. A multimodal differential diagnostic approach using complementary laboratory indicators is warranted to avoid unnecessary examinations and interventions, thereby reducing the waste of medical resources and preventing potential adverse events associated with inappropriate treatment.